Real spectra for the non-Hermitian Dirac equation in 1+1 dimensions with the most general coupling - Santos, V. G. C. S. dos [UNESP]; Dutra, Alvaro de Souza [UNESP]; Hott, M. B. [UNESP] (Elsevier B.V., 2009)
The most general combination of couplings of fermions with external potentials in 1 + 1 dimensions, must include vector, scalar and pseudoscalar potentials. We consider such a mixing of potentials in a PT-symmetric time-independent Dirac equation. The Dirac equation is mapped into an effective PT-symmetric Schrodinger equation. Despite the non-hermiticity of the effective potential, we find real energies for the fermion. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Dirac equation; Non-Hermitian potentials; PT symmetry; Exact solutions